2017
DOI: 10.1016/j.vaccine.2017.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Protection against infectious bronchitis virus by spike ectodomain subunit vaccine

Abstract: The avian coronavirus infectious bronchitis virus (IBV) S1 subunit of the spike (S) glycoprotein mediates viral attachment to host cells and the S2 subunit is responsible for membrane fusion. Using IBV Arkansas-type (Ark) S protein histochemistry, we show that extension of S1 with the S2 ectodomain improves binding to chicken tissues. Although the S1 subunit is the major inducer of neutralizing antibodies, vaccination with S1 protein has been shown to confer inadequate protection against challenge. The demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…The reason was that rHBM-S1-N expressed both the S1 and N proteins of IBV and stimulated both the humoral and cellular immune responses simultaneously, therefore the subunit vaccine rHBM-S1-N performed better in the activation of virus-specific immune responses. Although the S1 subunit is the major inducer of neutralizing antibodies, vaccination with S1 protein couldn't confer adequate protection against challenge [17]. A previous study even found that the antigenicity of N protein is better than that of the spike protein [37].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The reason was that rHBM-S1-N expressed both the S1 and N proteins of IBV and stimulated both the humoral and cellular immune responses simultaneously, therefore the subunit vaccine rHBM-S1-N performed better in the activation of virus-specific immune responses. Although the S1 subunit is the major inducer of neutralizing antibodies, vaccination with S1 protein couldn't confer adequate protection against challenge [17]. A previous study even found that the antigenicity of N protein is better than that of the spike protein [37].…”
Section: Discussionmentioning
confidence: 97%
“…Hence, there is an urgent need to develop new, safe and effective vaccines to control the disease. Recombinant subunit vaccines have been shown to elicit strong humoral and cellular immune responses and be very safe [16][17][18]. Therefore subunit vaccines may serve as potential vaccine candidates in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these proteins, S glycoprotein is the major protective antigen carrying neutralizing epitopes and can induce efficient immune responses against IBV Galli, 1993, 1995;Kant et al, 1992). Notably, S protein can be cleaved into the amino-terminal S1 and carboxy-terminal S2 domains by a furine-like protease from the host (Cavanagh, 2007;Eldemery et al, 2017;Kusters et al, 1989). S1 is responsible for IBV attachment to host cells, whereas S2 contributes to viral fusion activity of IBV (Wickramasinghe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…S2 protein expressed from recombinant virus confers broad protection against challenge (Toro et al, 2014). Therefore, S2 protein has important roles in inducing protective immunity (Eldemery et al, 2017). Moreover, (Kusters et al, 1989) in S2 have been identified as broad or neutralizing epitopes for IBV (Andoh et al, 2018;Ignjatovic and Sapats, 2005).…”
Section: Introductionmentioning
confidence: 99%